Iowa Birdline update, February 20, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Email for the Iowa Birdline update for February 20, 1995. Highlights of the update include sightings of the continued presence of the Common Eider, Lesser Black-backed Gull, Great Black-backed Gull, Long-tailed Duck and a Snowy Owl. Also included are handwritten notes for the next week's update with sightings of an immature Northern Goshawk, twelve Short-eared Owls and two Long-eared Owls. Epson - sheet feed/flatbed